WORK PROFILE OF ACCREDIATED SOCIAL HEALTH ACTIVISTS (ASHAS) IN A TALUK OF RAICHUR DISTRICT, KARNATAKA: A CROSS – SECTIONAL STUDY (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Accrediated Social Health Activists (ASHAs) are the link between the community and health system in India. One of the primary component of NRHM is to provide every village in the country with a trained female community health activists called as ASHA. ASHAs are healthy volunteers, promoters of health services who are the key force of action at the grass root level. She is responsible for improved utilization and accountability of existing health services and also expected to bridge the gap between the health system and the community. Objectives: •    To study the work profile of ASHA’s •    To study the work satisfaction and difficulties faced by ASHA’s Methods: A cross sectional study conducted among ASHA workers, a pretested questionnaire was used to collect data on socio-demographic profile, morbidity status, nutritional status and mental health. Data were analyzed using SPSS version 22 IBM. Analyzed data is presented as descriptive statistics with suitable graphical and tabular form. Categorical data is presented as proportions and continuous data is presented as mean and SD. Results: A total of 301 ASHA workers were participated. 292(97.1%) covered a minimum population of 500 to 2000 population. 231(76.6%) have experience between 5 – 15 years. All 301 ASHA workers accompanied at least 1 pregnant women for ANC and visited at least 1 PNC case. Conclusion: The majority of ASHAs covered population as per the guidelines. Almost all ASHA workers were involved in maternal care, Child care and family planning activities but they were lagging behind in promotion of male sterilisation.